Ecophysiological response of Sorghum halepense populations to reduced rates of nicosulfuron - Acciaresi, Horacio Abel (2005)
The control and regrowth after nicosulfuron reduced rate treatment of Johnsongrass (Sorghum halepense L. Pers.) populations, from seven Argentinean locations, were evaluated in pot experiments to assess if differential performance could limit the design and implementation of integrated weed management programs. Populations from humid regions registered a higher sensibility to reduced rates of nicosulfuron than populations from subhumid regions. This effect was visualised in the values of regression coefficient of the non-linear models (relating fresh weight to nicosulfuron rate), and in the time needed to obtain a 50% reduction of photosynthesis rate and stomatal conductance. The least leaf CO2 exchange of subhumid populations could result in a lower foliar absorption and translocation of nicosulfuron, thus producing less control and increasing their ability to sprout and produce new aerial biomass. The three populations from subhumid regions, with less sensibility to nicosulfuron rates, presented substantial difference in fresh weight, total rhizome length and number of rhizome nodes, when they were evaluated 20 week after treatment. In consequence, a substantial Johnsongrass re-infestation could occur, if rates below one-half of nicosulfuron labeled rate were used to control Johnsongrass in subhumid regions.